Efficient Protocols based on Probabilistic Encryption using Composite Degree Residue Classes - Damgård, Ivan B.; Jurik, Mads J. (BRICS Report Series, 2000)
We study various applications and variants of Paillier's probabilistic encryption scheme. First, we propose a threshold variant of the scheme, and also zero-knowledge protocols for proving that a given ciphertext encodes a given plaintext, and for verifying multiplication of encrypted values. We then show how these building blocks can be used for applying the scheme to efficient electronic voting. This reduces dramatically the work needed to compute the final result of an election, compared to the previously best known schemes. We show how the basic scheme for a yes/no vote can be easily adapted to casting a vote for up to t out of L candidates. The same basic building blocks can also be adapted to provide receipt-free elections, under appropriate physical assumptions. The scheme for 1 out of L elections can be optimised such that for a certain range of parameter values, a ballot has size only O(log L) bits. Finally, we propose a variant of the encryption scheme, that allows reducing the expansion factor of Paillier's scheme from 2 to almost 1.